Upaya Humas Polda Jatim Dalam Meningkatkan Pesan Informatif Melalui Konten Humanis Pada Akun Instagram @humaspoldajatim - Abel Rahma Putri; Julyanto Ekantoro; Tira Fitriawardhani (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to examine the efforts of the East Java Regional Police Public Relations Division in improving the quality of informative messages through humanistic-themed content on the Instagram account @humaspoldajatim. Digital developments demand the delivery of information that is fast, accurate, and easily understood, making Instagram a strategic medium for public communication with the community. This research focuses on the implementation of a humanistic approach and the enhancement of content quality in building audience understanding and engagement.This study employs a qualitative descriptive method using observation, interviews, and documentation techniques, which are then analyzed through the stages of fact finding, planning, communication, and evaluation based on Cutlip & Center’s theory. The results indicate that the Public Relations Division of the East Java Regional Police consistently applies humanistic elements in its content, including empathetic language, ethical visuals, and clear, non-judgmental information. The content also continuously adapts to digital trends, enabling it to reach a wider audience and enhance the relevance of messages within the community.The findings indicate that improving content quality through a humanistic approach plays a significant role in enhancing informative messages, strengthening public trust, and building a more modern image of the police institution. The utilization of Instagram features such as feeds, reels, stories, and captions is optimized to deliver valuable, easily understood information with emotional closeness to the public. Thus, a communication strategy based on humanistic content is able to foster a harmonious relationship between the police and the community in the digital era.